HUBUNGAN FINANCIAL TECHNOLOGY TERHADAP PERKEMBANGAN UMKM DI KOTA BANDA ACEH - Aviqa Humaira; Ferayanti Ferayanti (Fakultas Ekonomi dan Bisnis UNSYIAH, 2022)
AbstractThis research was conducted with the aim of knowing the relationship of financial technology to the development of MSMEs in Banda Aceh City. The data used in this study are primary and secondary data, in which the primary data was obtained through a questionnaire that had been distributed to 155 respondents who were obtained using the Slovin formula and met the required criteria. To determine the correlation between variables, the Spearman rank analysis test was used. The results of this study indicate that the financial technology variable has a positive and significant relationship to the development of MSMEs in Banda Aceh City. This research is expected to be input for the government to pay more attention to the MSME sector which still lacks technological knowledge.Keywords: Financial Technology, MSMEs, Correlation, Banda Aceh.